Congruence in Corporate Social Responsibility: Connecting the Identity and Behavior of Employers and Employees - Haski-Leventhal, Debbie; Roza, Lonneke; Meijs, Lucas C. P. M. (Journal of business ethics, 2017)
The multi-disciplinary interest in social responsibility on the part of individuals and organizations over the past 30 years has generated several descriptors of corporate social responsibility (CSR) and employee social responsibility (ESR). These descriptors focus largely on socially responsible behavior and, in some cases, on socially responsible identity. Very few authors have combined the two concepts in researching social responsibility. This situation can lead to an oversimplification of the concept of CSR, thereby impeding the examination of congruence between employees and organizations with regard to social responsibility. In this article, we connect two dimensions of social responsibility—identity and behavior—to build a Social Responsibility Matrix consisting of four patterns for classifying the social responsibility of employees and employers: Low Social Responsibility, Identity-based Social Responsibility, Behavior-based Social Responsibility, and Entwined Social Responsibility. The positioning of employers and employees on the same matrix (as determined by internal, relational, and/or external factors) is vital for assessing the level of congruence between employers and employees with regard to social responsibility and for discussing the possible outcomes for both parties. These identity and behavior-based patterns, determinants, and levels of congruence connecting employees and employers form the foundation for the multi-dimensional, dynamic ESR-CSR Congruence Model, as exemplified in a case study. This contribution enhances the existing literature and models of CSR, in addition to improving the understanding of employee-employer congruence, thereby broadening the array of possibilities for achieving positive organizational outcomes based on CSR.